2002
DOI: 10.1101/gad.1003902
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila heterochromatic gene encoding poly(ADP-ribose) polymerase (PARP) is required to modulate chromatin structure during development

Abstract: Poly(ADP-ribose) polymerase (PARP) is a major NAD-dependent modifying enzyme that mediates important steps in DNA repair, transcription, and apoptosis, but its role during development is poorly understood. We found that a single Drosophila Parp gene spans more than 150 kb of transposon-rich centromeric heterochromatin and produces several differentially spliced transcripts, including a novel isoform, PARP-e, predicted to encode a protein lacking enzymatic activity. An insertion mutation near the upstream promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
235
0
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(254 citation statements)
references
References 47 publications
(53 reference statements)
17
235
0
2
Order By: Relevance
“…While in mammals the PARP family is rather large, only two PARP enzymes, a PARP-1 and a tankyrase-1 ortholog, have been reported in Drosophila (Tulin et al, 2002). In agreement, PARP-10 orthologs could be identified neither in Drosophila nor in Caenorhabditis elegans (data not shown).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…While in mammals the PARP family is rather large, only two PARP enzymes, a PARP-1 and a tankyrase-1 ortholog, have been reported in Drosophila (Tulin et al, 2002). In agreement, PARP-10 orthologs could be identified neither in Drosophila nor in Caenorhabditis elegans (data not shown).…”
Section: Discussionsupporting
confidence: 60%
“…In agreement, PARP-10 orthologs could be identified neither in Drosophila nor in Caenorhabditis elegans (data not shown). In Drosophila, PARP-1 is required for chromatin organization and is associated with areas of high transcriptional activity and decondensed chromatin (chromosomal puffs) (Tulin et al, 2002;Tulin and Spradling, 2003). Gene activation in response to stress and steroid hormones results in an increase in poly (ADP-ribosyl)ated proteins at the responsive loci, which is required to obtain normal-sized puffs and efficient gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…PARP-1 has been linked to multiple events for transcriptional regulation in development. [61][62][63][64] A large body of evidence shows that PARP-1 is activated during the inflammatory response, contributing to tissue damage. Accordingly, pharmacological inhibition of PARP-1 has shown therapeutic efficacy in animal models of inflammation such as ischemia-reperfusion, 60 chronic colitis, 65 asthma, 66 autoimmune encephalomyelitis, 67 diabetes mellitus, 68 and PARP À/À mice are protected from endotoxic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that PARP1 regulates the transcription of these genes by inducing chromatin loosening at targeted genetic loci (6,7). Finally, PARP1 establishes silent chromatin domains and represses retrotransposable elements (8).…”
mentioning
confidence: 99%
“…Closing these gaps in our current knowledge is complicated because the presence of 18 paralogous PARP proteins (9) in mammals most likely results in corresponding functional redundancies. The Drosophila genome (8,10,11) encodes only a single nuclear PARP (PARP1), making this animal an invaluable model system for the study of PARP functions.…”
mentioning
confidence: 99%